Prescribed Performance Fuzzy Resilient Control for Nonlinear Systems Under DoS Attacks - Zhang, Lili; Che, Wei-Wei; Deng, Chao; Wu, Zheng-Guang (IEEE transactions on systems, man, and cybernetics. Systems, 2023)
This article investigates the prescribed performance security control problem for nonlinear systems subject to denial-of-service (DoS) attacks. An attack compensator is adopted to model the unavailable output signal when the attack is active. Based on the designed attack compensator, a fuzzy estimator is developed to approximate the unmeasurable state variables. Further, a security tracking control method is proposed by combining the fuzzy estimator and the novel attack-dependent barrier Lyapunov function. It can steer the tracking errors to the predetermined neighborhood around the origin in the predefined settling time. Meanwhile, all the closed-loop signals are bounded under DoS attacks. Compared with the existing conclusions with DoS attacks, the tracking accuracy and the time of achieving the tracking can be given in advance. Finally, two comparison simulations verify the validity of the designed security controller.